2005
DOI: 10.7861/clinmedicine.5-3-230
|View full text |Cite
|
Sign up to set email alerts
|

Is the NHS willing to help clinicians and patients reduce uncertainties about the effects of treatments?

Abstract: -Uncertainty is an inevitable component of clinical practice. Clinicians have a responsibility to minimise it by keeping up-to-date with current knowledge: but what is the responsibility of individual clinicians in reducing collective uncertainty? In all fields of medicine there are important questions relevant to both patients and clinicians, which can be answered only by clinical research. Unfortunately, much of the clinical research that attracts funding does not address the questions that both patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…smoking cessation strategies), manoeuvres to reduce weight in overweight and obese patients, coping strategies, assessment of different settings for providing treatment, and educational interventions. The conduct and publication of independent clinical research taking a broader view on disease management should be encouraged 44 . Public funding sources should be considered for supporting independent research.…”
Section: Discussionmentioning
confidence: 99%
“…smoking cessation strategies), manoeuvres to reduce weight in overweight and obese patients, coping strategies, assessment of different settings for providing treatment, and educational interventions. The conduct and publication of independent clinical research taking a broader view on disease management should be encouraged 44 . Public funding sources should be considered for supporting independent research.…”
Section: Discussionmentioning
confidence: 99%
“…The issues need discussion not only in the context of undergraduate education but even more importantly in the postgraduate training of doctors who need to understand the different notions of uncertainty and how to handle them. Furthermore, resolution of clinical uncertainties should be addressed wherever possible by NHS clinical research, a seriously neglected area addressed in this issue by Chalmers et al 15 The College's Ethics Committee is also discussing approaches to uncertainties in clinical practice. But education regarding uncertainties needs to go beyond that of doctors alone.…”
Section: The Way Forwardmentioning
confidence: 99%
“…Uncertainty can affect any type of healthcare decision that practitioners may make, such as assessment, diagnosis, intervention, communication, referral, service delivery and organisation, and information-seeking [15]. It has been suggested that increasing the availability of high quality research evidence on topics relevant to patients and healthcare professionals is one way of tackling uncertainties that arise from lack of scientific data [16]; such progress would this requires that the right research is commissioned and conducted.…”
Section: Introductionmentioning
confidence: 99%